New locations of rare species of higher plants in south-west region of Zhytomyr Polesye - V.I. Melnik (Інтродукція Рослин, 2010)
New locations of 8 rare species of higher plants in south-west region of Zhytomyr Polesye are described. Among them 2 species of moss – Cinсlidotus fontinaloides (Hedw.) A. Beauv., Fontinalis antipiretica Hedw., 2 species of ferns – Matteuccia struthiopteris (L.) Tod., Phegopteris connectilis (Michx.) Watt and 4 species of flowering plants – Phyteuma spicatum L., Polemonium caeruleum L., Genista germanica L., Dactylorhiza majalis (Reichenb.) P.F. Hunt & Summerhayes. Geographical distribution and habitats of these species in territory of Zhytomyr Polesye are considered.